THE STUDY OF SUCCESS FACTORS FOR ENTREPRENEURS OF STEEL PROCESSING FIRMS IN TAIWAN - Yen-Se Li; Te Tsai Lu; Chih Wei Chiang; Shen Lin Chen (Graduate Program of Universitas Tarumanagara, 2025)
Studies in the past have not been founded in regarding steel processing industry with the perspective of Entrepreneur, and this led to the motivation of this study. The main purpose of this study is to review the success factors for entrepreneurs of steel processing firms from the perspective of Entrepreneur. In this study, Taiwan steel processing industry, entrepreneurship, entrepreneur and critical success factor literature as the theoretical basis, and five productions of steel processing products professional firms for the study. In addition, the research method are adopted in this study are literature review and in-depth interviews, analysis of steel processing industry conditions and to examine the steel processing firms' first business process and key success factors. In the meantime, we also to find out the case, how can professional firms in the highly competive environment, the establishment of a unique competitive advantage to the follow-up for people wishing to enter the steel processing industry. Finally, this study found that the professional firms success and have the following nine key factors: (1) management skills; (2) product differentiation; (3) financial control; (4) work experience; (5) risk attitude; (6) economic condition; (7) venture capital; (8) start-up team; (9) organizational flexibility.